Drinking Motives As Mediators of the Associations between Reinforcement Sensitivity and Alcohol Misuse and Problems - Studer, Joseph; Baggio, Stéphanie; Dupuis, Marc; Mohler-Kuo, Meichun; Daeppen, Jean-Bernard; Gmel, Gerhard (Frontiers in Psychology, 2016)
Alcohol may be used and misused for different reasons, i.e., to enhance positive affect and to cope with negative affect. These to pathways are thought to depend on two distinct and relatively stable neurobiological systems: the behavioral activation (BAS; i.e., fun seeking, drive, reward responsiveness) and behavioral inhibition (BIS) systems. This study investigates the associations of BAS and BIS sensitivity with risky single-occasion drinking and alcohol use disorder in a representative sample of 5362 young Swiss men. In order to better understand the contribution of more proximal motivational factors in the associations of BIS and BAS with alcohol outcomes, mediations via drinking motives (i.e., enhancement, social, coping, conformity) was also tested. Risky single-occasion drinking and alcohol use disorder were positively associated with fun seeking and negatively with reward responsiveness. Drive was negatively associated with risky single-occasion drinking. BIS was positively associated with alcohol use disorder and negatively with risky single-occasion drinking. Positive associations of fun seeking with risky single-occasion drinking and alcohol use disorder were partially mediated mainly by enhancement motives. Negative association of drive with risky single-occasion drinking was partially mediated by conformity motives. The negative reward responsiveness—alcohol use disorder association was partially mediated, whereas the negative reward responsiveness—risky single-occasion drinking association was fully mediated, mainly by coping and enhancement motives. The positive BIS–alcohol use disorder association was fully mediated mainly by coping motives. Fun seeking constitutes a risk factor, whereas drive and reward responsiveness constitute protective factors against alcohol misuse and disorder. BIS constitutes a protective factor against risky single-occasion drinking and a risk factor for alcohol use disorder. The results of the mediation analysis suggest that prevention strategies targeting coping and enhancement motives may reduce the risk associated with high BIS and with high fun seeking, respectively.